Synthesis and Antimicrobial Activity of Some New Schiff Bases, 4-Thiazolidinones and 2-Azetidinones - Bhusare, S.R.; Ardhapure, S.S.; N. Jadhav, W.; P. Pawar, R.; B. Vibhute, Y. (Asian Journal of Chemistry, 2010)
Some new heterocyclic Schiff bases 1were synthesized from 2-amino-α-naphthothiazole. Further these heterocyclic Schiff bases were converted into 4-thiazolidinones 2and 2-azetidinones 3by the action of mercaptoacetic acid and chloroacetyl chloride respectively. Structure elucidation of compounds 1, 2 and 3 has been made on the basis of elemental analysis, IR and 1H NMR data. The biological screening data of 1, 2 and 3 are also presented.